Study on Extraction Separation of Thioarsenite Acid in Alkaline Solution by CO32--Type Tri-n-Octylmethyl-Ammonium Chloride - Yan, Kang; Liu, Liping; Zhao, Hongxing; Tian, Lei; Xu, Zhifeng; Wang, Ruixiang (Frontiers in Chemistry, 2021)
To overcome the problem of arsenic separation and enrichment from an alkaline leaching solution in arsenic-containing dust, a CO32--type tri-n-octylmethyl-ammonium chloride (TOMAC) method for extracting thioarsenite is proposed in this paper. Considering an alkaline leaching solution as the research object, after vulcanization pretreatment, TOMAC transformation and organic phase saturated extraction capacity were measured, and the extraction mechanism was preliminarily studied. First, Cl--type quaternary ammonium salt was effectively transformed to HCO3--type by treating organic phase with saturated NaHCO3 five times. TOMAC was effectively transformed from HCO3-- to CO32--type by alkaline washing with 1.0 mol/L NaOH solution; this washing was repeated thrice. Thereafter, the effects of organic phase composition, phase ratio, extraction time, and temperature on the extraction and separation of arsenic were investigated. The results show that under the conditions of 30% CO32--type TOMAC + 15% sec-octanol + 55% sulfonated kerosene, VO/VA = 1/1, and 5 min extraction at room temperature, the single-stage extraction rate of AsIII is 85.2%. The AsIII concentration in raffinate can be reduced to less than 1.33 × 10-3 mol/L by four-stage countercurrent extraction, and the extraction rate of AsIII can exceed 98.4%.